Pengaruh Penerapan Model Pembelajaran Number Head Together Terhadap Motivasi Belajar Pkn Siswa Sekolah Dasar - M Salam; Fajar Surya Ningsih (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
This study aims to determine the effect of the Number Head Together learning model on PKn learning motivation of VA students in SDN 146 / IV Jambi City. The research method used by the researcher in this study was an experimental study of One-Group Pretest-Posttest Design with research subjects in class VA SDN 146 / IV Kota Jambi. Based on the results of the study data analysis the influence of the Number Head Together model and learning motivation was r_xy 0.81 with very strong category. After analyzing the magnitude of the significance of the effect of the Number Head Together model on learning motivation with questionnaire data, namely F_count> F table or 417.144> 4.28. It is concluded that the effect of variable X on Y is significant and Ha is accepted while Ho is rejected. In addition to carrying out the significance test, the linearity test with the following values ​​was carried out, for price questionnaire data F_count = 9.45 and F table = 9.68 (9.45 ≤ 9.68) with a significant level (α) = 0.05, and numerator = 16, and no denominator 5. So, it can be concluded that the variable Number Head Together learning model data on PKn learning motivation in VA students of SDN 146 / IV in Jambi City has a Linear pattern. From the discussion above, it can be concluded that there is a significant influence between the Number Head Together learning model on PKn learning motivation of VA students in SDN 146 / IV Jambi City.